2019
DOI: 10.1159/000499735
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Inhibition of Connexin 36 Ameliorates Fetal Brain Injury Induced by Maternal Noninfectious Fever in Mice

Abstract: Prenatal fever could result in brain function impairments in the offspring. The present study investigated the effect of interleukin-6 (IL-6)-induced maternal fever on the offspring and the involvement of connexin 36 in this process. Pregnant C57BL/6J mice were injected with IL-6 on gestational day 15. The levels of iNOS and COX-2 were measured as an index of neuroinflammation in the brain of newborn pups. Offspring were treated with the connexin 36 (Cx36) inhibitor mefloquine at postnatal day (P)1–P3 or at P4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Evidence indicated that Cx36 took part in several pathophysiological activities, like injury and inflammation (Wang et al., 2019 ), which was closely related to depressive disorder. Therefore, we first sought to see how Cx36 changed in depressive model induced by CUMS.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence indicated that Cx36 took part in several pathophysiological activities, like injury and inflammation (Wang et al., 2019 ), which was closely related to depressive disorder. Therefore, we first sought to see how Cx36 changed in depressive model induced by CUMS.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, MFQ, an FDA-approved antimalarial compound, is used for the prevention or treatment of mild and moderate malaria 20 , with neuropsychiatric side effects 14,18,21 . Later, it was discovered that MFQ specifically blocks Cx36 GJC, contributing to these side effects, such as spreading depression, NMDAR-mediated neuronal death, tremor, motor deficits, convulsant, stage IV seizures, cell death upon oxygenglucose deprivation, and hypersensitivity to pain [22][23][24][25][26][27][28][29] . Additionally, it is noteworthy that MFQ exhibits 10-to 100-fold higher sensitivity to Cx36 (IC50 value of 310 nM) and Cx50 (IC50 value of 1.1 μM) compared to other connexins.…”
Section: Introductionmentioning
confidence: 99%